European Painting and Nepali Painting: Artistic Exchange and Adaptation in the19th Century (SIRJANĀ – A Journal Of Arts and Art Education, 2025)
The initiation of Western painting in Nepal began after the Sugauli treaty, notably through the work of Raj Man Singh Chitrakar and a few other artists who depicted birds, animals, monuments, landscapes using Camera Lucida, pencil, ink, and water colour under the guidance of British Resident Brian Houghton Hodgson. Bhaju Man Chitrakar accompanied Prime Minister Jung Bahadur Rana to Europe, where he was exposed to European art techniques. Upon his return, he produced realistic portraits of the King, Prime Minister, royal family members, along with hunting scenes and still life in European style. Similarly, Henry Ambrose Oldfield and his wife Margaret created hundreds of paintings portraying Kathmandu Valley's architecture, landscapes, and people. The introduction of photography by Clarence Comyn Tayler, who captured portraits of the royal family, marked a significant shift in Nepal's visual documentation practices. Later, Dirgha Man Chitrakar travelled to England and France, and he used large-format cameras, depicting wall decorations, theatrical backdrops, and oil portraits of royal and Rana families. This qualitative study, based on limited secondary sources, concludes that a few Nepali artists adopted European art styles through exposure to foreign residents and travel abroad. The works of Raj Man Chitrakar and Henry Ambrose Oldfield continue to assist the restoration of Nepal's historical monuments.